1935
DOI: 10.1172/jci100737
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein in Hemorrhagic Bright's Disease

Abstract: The comparatively few accurate studies of the nitrogen balance which have been made during the chronic active stage of nephritis have been concerned chiefly with the quantitative aspect of the protein requirement (17). Little attention has been given to the kind of protein fed and its effect upon hypoproteinemia, proteinuria and the storage of protein in the tissues.2 The problem of hypoproteinemia is of especial interest, since no satisfactory means of increasing the concentration of the serum proteins of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1936
1936
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Certainly with respect to the proteins here tested, the potency ratios are not so widely different as to warrant the administration of any one protein in preference to another. This conclusion is supported by the observations of Keutmann and Bassett (16), who applied the findings of Whipple and associates in feeding three patients with degenerative Bright's disease. No really distinct, significant differences were detected in the effect of the protein supplements tested.…”
Section: Discussionsupporting
confidence: 71%
“…Certainly with respect to the proteins here tested, the potency ratios are not so widely different as to warrant the administration of any one protein in preference to another. This conclusion is supported by the observations of Keutmann and Bassett (16), who applied the findings of Whipple and associates in feeding three patients with degenerative Bright's disease. No really distinct, significant differences were detected in the effect of the protein supplements tested.…”
Section: Discussionsupporting
confidence: 71%
“…In evaluating these dietary changes the potency ratio was assumed to be independent of the amount of protein in the diet. However, it has been shown that the coefficient of utilization of an essential dietary component, in this case the protein (7)(8)(9), decreases when an excess of the substance is fed. 5.…”
mentioning
confidence: 99%
“…Liu and Chu (11), Keutmann and Bassett (12), and Farr (13) have all found an "optimum" intake of about 3.0 gin. of protein per kg.…”
Section: Discussionmentioning
confidence: 99%